2012
DOI: 10.1016/j.susc.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The structure of epitaxial V2O3 films and their surfaces: A medium energy ion scattering study

Abstract: Medium energy ion scattering (MEIS), using 100 keV H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 48 publications
(73 reference statements)
2
21
2
Order By: Relevance
“…A variety of oxide thin films have been fabricated on the Au(111) surface including TiO x [18,23,24,27], FeO x [22,34], VO x [35][36][37][38], CoO [39][40][41], MoO 3 [28,42,43], MgO [19,[44][45][46], CeO x [25], ZnO [47] and BaO x [48]. The growth of ultrathin oxide films on the Au(111) surface usually lifts the herringbone reconstruction due to the strong interaction between the film and the substrate.…”
Section: Structure Of the Oxide Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of oxide thin films have been fabricated on the Au(111) surface including TiO x [18,23,24,27], FeO x [22,34], VO x [35][36][37][38], CoO [39][40][41], MoO 3 [28,42,43], MgO [19,[44][45][46], CeO x [25], ZnO [47] and BaO x [48]. The growth of ultrathin oxide films on the Au(111) surface usually lifts the herringbone reconstruction due to the strong interaction between the film and the substrate.…”
Section: Structure Of the Oxide Filmsmentioning
confidence: 99%
“…5.3), and for a number of years there were conflicting views concerning the detailed atomic structure of the film [51,52]. While XPS and STM suggested a surface terminated with a vanadyl (V=O) group [37,53], ion scattering investigations and ion beam triangulation supported the reconstructed O 3 model [35,36,38]. More recently, this controversy on the V 2 O 3 (0001) termination has been revisited and resolved via a ; V s = −0.12 V; I t = 0.5 nA) [18] combination of I-V LEED, STM, fast atom scattering and DFT, indicating that the vanadyl termination is thermodynamically more stable [54].…”
Section: Structure Of the Oxide Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 61.05.jh, 68.47.Gh Vanadium oxides find significant interest in basic research and are of technological importance because of their metal to insulator transitions and applications in oxygen transfer catalysis [1][2][3][4][5]. The surface termination is of decisive relevance for both classes of applicationsthis is obvious for the area of catalysis, but the influence on phase transitions, at least in near-surface layers, has also been shown [6], For V20 3(0001), a number of studies have been published, but there is still an ongoing debate about its termination [7][8][9][10][11][12][13][14].For almost a decade, the V20 3(0001) surface prepared under ultrahigh vacuum (UHV) conditions was assumed to be vanadyl terminated. This conclusion was based mainly on the presence of an intense vanadyl signal in vibrational spectra [7,8], but scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy, and near edge X-ray absorption fine structure data also supported this view [7,8,15].…”
mentioning
confidence: 99%
“…Guided mainly by the presence of an intense vanadyl induced feature in vibrational spectra [10,11] is was concluded that the surface should be terminated by a layer of vanadyl groups. This was questioned some years ago by studies which reported that the surface should be terminated by a quasi-hexagonal oxygen layer [18][19][20]. A later I/V-LEED (LEED = low energy electron diffraction; I/V-LEED = LEED intensity analysis) study could show that the initial picture of a vanadyl terminated surface is probably correct [21,22] and therefore we will use the term 'vanadyl terminated' throughout this text.…”
mentioning
confidence: 99%